Exploring The Potential of Gonggong Sea Snails (Laevistrombus Sp.) in Biotechnology as a Source of Natural Compounds for Wound Healing - Rizka Fadilah; Zen Hafy; Veny Larasati (Green Publisher Indonesia, 2025)
The gonggongsea snail(Laevistrombussp.) is a typical marine life of the Riau Islands that contains various bioactive compounds with potential as wound healing agents based on natural ingredients. This study aims to evaluate the potential of gonggong seasnailextract through a literature review of articles obtained from PubMed, ScienceDirect, Google Scholar, and Scopus. Analysis of 18 articles showed that gonggongsea snailscontain histone protein H2A, antimicrobial peptides, flavonoids, alkaloids, saponins, as well as essential amino acids such as arginine, proline, and glycine that work synergistically throughout the wound healing phase. The compound plays a role in suppressing inflammation through inhibition of the NF-κB pathway and increasing IL-10, supporting the proliferation phase by stimulating angiogenesis and collagen synthesis, and improving the remodeling phase through improved tissue quality and antioxidant activity. Histological assessment can use the SPOT score system to show relevant parameters to evaluate the effectiveness of natural ingredients in wound healing. The results of this study confirm that gonggongsea snailextract has great potential to be developed as an effective, safe, and sustainable wound therapy candidate, so experimental research is needed to validate molecular mechanisms and standardize formulations.